THE QUANTITATIVE ANALYSIS OF POLIPHENOLIC COMPOUNDS IN DIFFERENT PARTS OF THE ARTICHOKE (cynara scolymus L.) DEPENDING ON GROWTH STAGE OF PLANTS - Andrzej Sałata; Robert Gruszecki (Acta Scientiarum Polonorum: Hortorum Cultus, 2010)
A diversity of active substances that are in the artichoke plants includes it into the group of medicinal plants of broad-spectrum performance. The research conducted in the years 2006–2008 included valuation of poliphenolic compounds content in different parts of artichoke plants during vegetative and generative growth (roots, petioles, leaves, immature and flower at beginning of flowering). The total content of poliphenolic compounds in the reduction on caffeic acid was marked in dried herb with the spectrophotometrical method with the Arnova reagent. The content of poliphenolic acids (caffeic, chlorogenic, ferulic and cynarine) was marked with high performance liquid chromatography (HPLC). The undertaken studies show that there are significant differences with respect to the content of poliphenolic compounds in different parts of artichoke plants. Definitely more total phenolic acids were accumulated in leaves during the vegetative growth (3.167% on average) and in young, immature buds during generative growth (3.730% on average). The chlorogenic acid and cynarine were the main compounds among poliphenolic acids. The content of poliphenolic acids was decreasing with age of plants as young immature artichoke buds had more chlorogenic acid and cynarine than mature heads at the beginning of flowering. The content of caffeic and ferulic acids in the artichoke herb depended on the growth phase of plants. Plants accumulated more caffeic acid in leaves during vegetative growth and ferulic acid in buds during generative growth.